Welfare Status and Type of Floor Associated with Hock Lesions in Dairy Cattle of University, Research and Private Farm of Chitwan District - Jha, R.; Gurung, Y. B.; Singh, D. K. (Nepalese Veterinary Journal, 2019)
This research is an investigation of the prevalence of, and factors associated with, hock lesions on dairy cattle of University, Research and Private farm of Chitwan district. Cemented floor (n = 141), Muddy floor (27), Floor with Mat (35) and brick paved floored animals (n = 33) were visited. Cows were scored for hock (tarsus) lesions on a 3 point scale combining the attributes ofhair loss, broken skin, and swelling. Type of farm (University, Research and Private) and type of floor measures were taken which were hypothesized to be risk factors for lesions. On university (AFU), research (NARC) and private farms the mean level prevalence of hock lesions was 1.827±0.384, 1.4±0.4905 and 1.465±0.68 respectively. On cemented floor, muddy floor, floor with rubber mat and brick paved floor, the mean prevalence of hock lesions was 1.63±0.489, 1.0165±0.577, 1.343±0.481 and 1.83±0.44 respectively. In conclusion muddy floor was associated with reduced hock lesions scoring compared to cemented, brick and rubber mat.